THE RISK PERCEPTION OF COVID-19 IN INDONESIA - Atikah Fatmawati; Sylvia Yunike Hendrayani (Jurnal Vokasi Keperawatan (JVK), 2020)
The COVID-19 pandemic was a surprising event in early 2020. Patients were confirmed positive and patients died increasingly showing an increasing trend. Good knowledge and perception from the community are needed to break the chain of distribution of COVID-19. The purpose of this study was to determine the description of public perceptions about the risk of COVID-19 in Indonesia. This research is a descriptive study and used 134 respondents from several regions in Indonesia and taken used an accidental sampling technique. Data collection using a questionnaire consisting of 19 statements to measure people's perceptions about the risk of COVID-19. The results showed that the level of public perception in this study was 85.8%. The results of this study can be used as a basis for relevant parties in planning actions and also in formulating policies to break the chain of COVID-19 distribution in Indonesia.